(untitled) (Bangladesh Journal of Bioethics, 2012)
Knowledge is the multidimensional outcome of human intellect. Intellectual Property Rights system (IPRs) is considered from economic and legal aspect as the ownership rights for the excessive use of innovation and creative work. IPRs are measured to encourage innovation, promote investment in S&T and make the technologies for public benefit. But history shows that from the time of industrial revolution in Europe and during twentieth century in the North America and Japan, IPRs contribute to the S&T driven economic growth. Therefore, there is a fair and consistent relationship between strength of IPRs and per capital income. A recent study of World Bank suggested that the major beneficiaries of IPRs in terms of enhanced value of patents are the developed countries with USA along made an annual gain of US 20 billion while developing country face an annual loss of 7.5 billion on royalties and license fees. Moreover, for the developing county, while indigenous technological capability is a significant determinant to economic growth and poverty reduction, no exact relationship has been established between the IPRs and economic growth. Developed countries and business corporations who are benefited directly from IPRs regime insist on implementation of strong IPRs for all countries. Need for strong IPRs for developing and least developed countries are discussed. Strong IPRs for all countries whether it leads to transfer of wealth from poor countries to rich countries to further widen the economic divide is a major ethical concern. DOI: http://dx.doi.org/10.3329/bioethics.v1i3.9633 Bangladesh Journal of Bioethics 2010; 1(3): 43-46